1994
DOI: 10.3354/meps110135
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic coupling of reef fish replenishment and oceanographic processes

Abstract: Oceanographic processes have been shown to play a pivotal role in the control of recruitment variability in some commercial, northern temperate fish populations. This study investigates the link between inter-annual changes in larval supply and wind stress for unexploited reef fish populations at Lizard Island, northern Great Barrier Reef. For the first time, this relationship is analysed separately for front-reef and back-reef habitats and results for 3 major reef fish familes (Pomacentridae, Apogorudae, Blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 21 publications
0
55
1
Order By: Relevance
“…Our results are consistent with the suggestion that larval growth and condition may be an important determinant of survivorship in the plankton (Suthers 1998), as has recently been shown to be the case in post-settlement reef fishes (Booth and Hixon 1999;Searcy and Sponagule 2002;Vigliola and Meekan 2002;but see McCormick and Kerrigan 1996). Our findings contrast with much of the current research on recruitment variability in tropical fishes, which has typically emphasised the role of larval transport (Shenker et al 1993;Milicich 1994;Kingsford and Finn 1997;Robertson et al 1999). Such studies have had little success in predicting recruitment intensity.…”
Section: Discussioncontrasting
confidence: 55%
“…Our results are consistent with the suggestion that larval growth and condition may be an important determinant of survivorship in the plankton (Suthers 1998), as has recently been shown to be the case in post-settlement reef fishes (Booth and Hixon 1999;Searcy and Sponagule 2002;Vigliola and Meekan 2002;but see McCormick and Kerrigan 1996). Our findings contrast with much of the current research on recruitment variability in tropical fishes, which has typically emphasised the role of larval transport (Shenker et al 1993;Milicich 1994;Kingsford and Finn 1997;Robertson et al 1999). Such studies have had little success in predicting recruitment intensity.…”
Section: Discussioncontrasting
confidence: 55%
“…Physical processes that have been associated with the transport of late-stage larvae include wind and storm events (Shenker et al 1993;Milicich 1994;Thorrold et al 1994); tides (see for review) and internal tidal bores (Pineda 1991;Leichter et al 1998;Findlay and Allen 2002), waves, and slicks (Shanks 1983;Kingsford and Choat 1986); and onshore flow at depth (Cowen and Castro 1994;Sponaugle and Cowen 1996a;Paris-Limouzy 2001). Recirculating features such as current eddies have been hypothesized to function both as larval retention mechanisms (e.g., Sale 1970;Hamner and Hauri 1981;Lee et al 1994) and as onshore transport mechanisms (Limouzy-Paris et al 1997;Yeung et al 2001).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, only a few studies have explained the differences found in the recruitment intensity of fish as due to upwelling or downwelling flow (Reiss and McConaugha 1999;Miller and Shanks 2005), and none of these have referred to coral-reef fishes. Since upwelling and downwelling currents are usually wind-driven (but can also result from thermohaline forces), it is possible that some studies that found a correlation between the abundance of fish larvae and their transport to the reef by winds (Shenker et al 1993;Milicich 1994;Kingsford and Finn 1997) were in fact dealing with up-and downwelling currents (Shenker et al 1993).…”
mentioning
confidence: 99%